Boosting polysulfide confinement and redox kinetics via ZnSe/NC@rGO as separator modifier for high-performance lithium-sulfur batteries. (20th March 2023) - Sun, Qian; Zhang, Yayun; Zhou, Hui; Ma, Cheng; Zhang, Yongzheng; Wang, Jitong; Qiao, Wenming; Ling, Licheng
Abstract: Although lithium-sulfur (Li-S) batteries have an unparalleled specific capacity, the notorious shuttle effect, and slow reaction kinetics severely inhibit their development. Herein, a composite composed of ZnSe nanoparticles with a nitrogen-doped (N-doped) carbon shell uniformly dispersed in reduced graphene oxide (ZnSe/NC@rGO) is designed as a separator modifier for Li-S batteries. The underlying mechanism of the ZnSe/NC@rGO modified separator is confirmed by both systemic electrochemical characterization and density functional theory (DFT) calculations. Graphene as a highly conductive skeleton promotes electrical conductivity, while N-doping provides additional adsorption sites for the immobilization of lithium polysulfides (LiPSs). Moreover, the polar ZnSe has good chemical adsorption capabilities for LiPSs and could lower the decomposition energy barrier of Li2 S, which effectively facilitates the catalytic conversion of polysulfides. In addition, the separator modifier is beneficial to the uniform deposition of lithium. Thus, the delicate catalyst can effectively suppress the shuttle effect and accelerate the redox reaction kinetics during the charging and discharging processes. When used as a separator modifier of Li-S batteries, ZnSe/NC@rGO delivers enhanced electrochemical performance, including a high capacity (1057 mAh g –1 at 0.2 C after 100 cycles) and excellent rate performance of 685 mAh g –1 at 3 C. The negligible capacity decay per cycle within 900 cycles at 1 C is as low as 0.043%. These findings not only provide a feasible method for boosting the electrochemical performance of Li-S batteries but also reveal that transition metal selenides have potential in energy storage as electrocatalysts.